Biotransformation of Methane and Carbon Dioxide Into High-Value Products by Methanotrophs: Current State of Art and Future Prospects - Sahoo, Krishna Kalyani; Goswami, Gargi; Das, Debasish (Frontiers in Microbiology, 2021)
Conventional chemical methods to transform methane and carbon dioxide into useful chemicals are plagued by the requirement for extreme operating conditions and expensive catalysts. Exploitation of microorganisms as biocatalysts is an attractive alternative to sequester these C1 compounds and convert them into value-added chemicals through their inherent metabolic pathways. Microbial biocatalysts are advantageous over chemical processes as they require mild-operating conditions and do not release any toxic by-products. Methanotrophs are potential cell-factories for synthesizing a wide range of high-value products via utilizing methane as the sole source of carbon and energy, and hence, serve as excellent candidate for methane sequestration. Besides, methanotrophs are capable of capturing carbon dioxide and enzymatically hydrogenating it into methanol, and hence qualify to be suitable candidates for carbon dioxide sequestration. However, large-scale production of value-added products from methanotrophs still presents an overwhelming challenge, due to gas-liquid mass transfer limitations, low solubility of gases in liquid medium and low titre of products. This requires design and engineering of efficient reactors for scale-up of the process. The present review offers an overview of the metabolic architecture of methanotrophs and the range of product portfolio they can offer. Special emphasis is given on methanol biosynthesis as a potential biofuel molecule, through utilization of methane and alternate pathway of carbon dioxide sequestration. In view of the gas-liquid mass transfer and low solubility of gases, the key rate-limiting step in gas fermentation, emphasis is given towards reactor design consideration essential to achieve better process performance.